Respuesta :
Answer:
0
Step-by-step explanation:
First, you need to try to get rid of the ().
To do this:
15 * 3 and 15 * x
This makes 45 and 15x after the = , so the formula is now:
15x + 45 = 45 + 15x
Now get the 15x to the left side. When a number switches sides, it becomes negative when positive and positive when negative. So in this case 15x will become -15x and the 45(on the left) becomes - 45
15x - 15x = 45 - 45
Answer: 0
15x + 45 = 45 + 15x
15x - 15x = 45 - 45
0x = 0 (*)
If we plug any real numbers of x to equation (*) we will always get 0 = 0
So the set of solutions of this question is all real numbers
15x - 15x = 45 - 45
0x = 0 (*)
If we plug any real numbers of x to equation (*) we will always get 0 = 0
So the set of solutions of this question is all real numbers